Growth Engines of the South? South Africa's, Brazil's and Turkey's market constellations in comparison - Alper Duman; Arne Heise (Izmir University of Economics, Department of Economics, 2009)
The world is experiencing its worst recession in 80 years. What started as US sub-prime financial turmoil has developed into the first global recession since the infamous "Great Depression" of the early 1930s. However gloomy the perspectives for the very short term are, there will be a recovery eventually. South Africa, Brazil and Turkey (SABT) are among those countries that may be expected as emerging market economies (EME) not only to continue to converge towards per-capita income levels of highly developed nations but also to be the best candidates - next to China and India - of serving as the locomotives of world GDP- and trade growth after the depression. Of course, whether SABT are not merely potentially in a position to create a brighter future for their people and the world economy but can transform such potentials into reality, depends on economic governance pursued by governments and collective actors in these countries. Therefore, it appears interesting to inquire into the macroeconomic governance structures of SABT in order to assess their capabilities for enhancing growth and employment and to converge to the OECD average in the medium to long run.
Keywords: O11; O17; P51; P52; 330; Market constellations; policy regimes; institutions; Post Keynesianism; comparative economic systems; Wirtschaftswachstum; Policy-Mix; Institutionelle Infrastruktur; Postkeynesianismus; Systemvergleich; Schwellenländer; Südafrika; Brasilien; Türkei